THU0492 Serum ACE for Sarcoidosis is not such an ACE Test. (23rd January 2014) - Alston, C.; Hull, R.; Sinclair, D.; Ledingham, J.; McCrae, F.; Shaban, R.; Thomas, L.; Wong, E.; Young-Min, S.
Abstract : Background: A serum angiotensin-converting enzyme (ACE) level can be elevated in patients with active sarcoidosis. This association was first described Dr Lieberman in 1975 (1 ). He looked at serum ACE levels in 200 control patients and 200 patients with chronic lung disease. He found that 15 of 17 patients with active sarcoidosis had a serum ACE level, which was greater than two standard deviations above the mean (1 ). As a result serum ACE levels are routinely tested in patients with suspected sarcoidosis. A serum ACE test has been reported to be elevated in 75% of patients with untreated sarcoidosis (2 ). The rate of false positive results is less than 10% (2, 3 ). Other granulomatous conditions which may cause an elevated ACE level are tuberculosis, primary biliary cirrhosis, Crohn's disease, leprosy and Gaucher's disease (2, 4 ). The sensitivity and specificity of the test are reported to be 60 and 70% respectively (5 ). A serum ACE analysis costs €11.5 per test in our laboratory. Methods: We have completed a retrospective evaluation of the serum ACE test at our busy district general hospital. The serum ACE tests which have been requested by the rheumatology department over the last six years have been reviewed. Over this time period, 130 tests were performed on 126 cases. Results: There were three positive results. The upper limit of normal in our laboratory is 92iu/L. None of these cases were ultimately diagnosed with sarcoidosis. The three cases were each diagnosed with seronegative inflammatory arthritis, Systemic Lupus Erythematosus and bilateral carpal tunnel syndrome. Consequently we found the false positive rate to be 100% (Specificity 0%). In our cohort there were 13 cases of sarcoidosis. All of the cases had a negative serum ACE level (False negative rate 100%, Sensitivity 0%). There were 12 cases of acute sarcoidosis, where a raised serum ACE level would have been expected. The one known case of chronic sarcoidosis was treated with sulphasalazine. The diagnosis of sarcoidosis was made with a positive biopsy (9/13 [69%]) or on clinical grounds (Bilateral Hilar lymphadenopathy on CXR at presentation 10/12 [83%], erythema nodosum 7/13 [54%]). Conclusions: In this study, serum ACE testing does not appear to have any diagnostic benefit whilst being a relatively expensive test. All our cases over a 6 year period had an ACE level in the normal range. We estimate that our department has spent €1500 on serum ACE testing over the last six years. This money could perhaps be spent more effectively. We suggest that a CXR combined with good clinical assessments are better diagnostic tools in our setting of a busy district general hospital. As a result of this study, our department has stopped requesting serum ACE levels. References: Lieberman J (1975). Elevation of serum angiotensin-converting-enzyme (ACE) level in sarcoidosis. American Journal of Medicine. Sep;59(3):365-72. Studdy PR, Bird R (1989) Serum angiotensin converting enzyme in sarcoidosis--its value in present clinical practice. Annuals Clinical Biochemistry. 1989;29 (pt 1):13 Baughman RP (2004) Pulmonary sarcoidosis. Clin Chest Med. 2004; 25 (3):521 Kelley, Harris, Ruddy and Sledge. 1993. Textbook of Rheumatology. Page 1429-33. 4th edition. WB Saunders Kamangar N. 2011. Sarcoidosis. e-medicine 2011 july http://emedicine.medscape.com/article/301914-workup Disclosure of Interest: None Declared